Genetic study in congenital heart defects - Hussain, Syed Abir; Wani, Nasir U din; Muzaffar, Tasneem; Dar, Abdul Majeed; Bhat, Mohammad Akbar; Rasool, Roohi; Bhat, Imtiyaz Ahmad; Singh, Shyam (International Journal of Research in Medical Sciences, 2019)
Background: Congenital heart diseases (CHD) are relatively common with a prevalence ranging from 3.7 to 17.5 per 1000 live births. Little is known about genetic link with respect to congenital heart disease. Iroquoise (Irx) homeobox genes have been widely studied and their expression in both developing and adult heart. Author tried to study the role of irx4 and irx5 genes in structural congenital heart disease, keeping the focus on study reported by Cheng Z et al. Methods: Author studied reported mutation site sequences in 25 various congenital heart disease patients and control healthy relatives of patients. It is a unique study and there has not been such a study reported in literature till date. Besides comparison with healthy related controls, author took cardiac tissue biopsy in patients while doing corrective cardiac surgery. However, blood samples were taken from controls due to ease of feasibility. Results: Although, there were no sequence variations in the studied exon regions, but author got a base pair sequence change at 6 bp intron region, which is near the exon splice site in irx4 gene. Besides two ASD patient’s male children (one child each) had ASD prompting us to believe some role of sex linkage. However later needs pedigree analysis and sex chromosome studies for further analysis. Conclusions: Gene sequence in the Kashmiri population is unique. There is possibility of role of irx genes in CHD. ASD might have sex linkage in some.